دور الحوافز الوظيفية في تحسين أداء موظفي مكتبات جامعة مصراتة: دارسة ميدانية (Journal of Academic Research, 2025)
This study was entitled Incentives and their Role in Improving the Performance of Misurata University Library Employees. The study aimed to introduce incentives, their types, their importance and their role in improving the performance of university library employees and their services, and to identify the fairness of the university’s incentive distribution system. The study used the descriptive analytical approach. The study population represented all library employees.  The University of Misrata, whose number is (73) employees, distributed among (18) libraries. The study sample was determined by (84.9%) of the original community, meaning it represents (62) employees of the library employees of the University of Misurata. When it was conducted, the study was based on the questionnaire and the study concluded with the following:  Incentives increase motivation and lead to improving performance and developing university library services at Misurata University. There is no justice in the incentive system in university libraries, and employees are in dire need of implementing